Education for administration. The Executive Master of Science in Nursing program: competencies and learning experiences...first in a 3-part series - Thomas J; Herrin D (Journal of Nursing Administration (JONA), 2008)
This is the first in a 3-part series describing an executive master of science in nursing program. Part 1 describes program development built on the American Organization of Nurse Executives' competencies and distinct features of the students' online and on-site learning experiences. Part 2 will discuss how the 14 Forces of Magnetism are integrated across the curriculum and the unique criteria for program admission. Finally, Part 3 will describe the use of the Robert Wood Johnson Executive Nurse Fellows Program as the model for learning activity and Benner's Novice to Expert theory for program evaluation.